Using Acemoglu and Robinson's concept to assess Leviathans in CECCs in the long term - Rafał Matera (Comparative Economic Research. Central and Eastern Europe, 2022)
The main objective of the paper is to use the following terms of Daron Acemoglu and James Robinson - Despotic, Real, Paper, Shackled Leviathans - to check and evaluate the state of democracy, governance and social power in Central and Eastern European Countries (CECCs). Six states were included in the study: Poland, Czechia, Slovakia (before 1993 Czechoslovakia), Hungary, Romania and Bulgaria. Based on a historical analysis, Leviathan types were identified in the interwar period, communism, and the transition time. In the most recent period (the twenty-first century), eight democracy and freedom indices were presented, which take into account the quality of governance, the state of institutions and the potential of social capital in the six CEECs. The usefulness of these indices for assessing whether (and when) a country managed to shackle Leviathan were checked.
Keywords: D7; H1; K4; N4; O5; P2; P5; 330; CEECs; Acemoglu & Robinson Concepts; Types ofLeviathan; Shackled Leviathan